Independent Validation of a Self-Report Version of the IBD Disability Index (IBDDI) in a Population-Based Cohort of IBD Patients. Issue 4 (15th March 2018) - Shafer, LA; Walker, JR; Chhibba, T; Ivekovic, M; Singh, H; Targownik, LE; Peyrin-Biroulet, L; Gower-Rousseau, C; Sarter, H; Bernstein, CN
Abstract: Introduction: A new clinician-administered inflammatory bowel disease (IBD) Disability Index (IBDDI) was recently developed and validated among a population in France. We aimed to validate the IBDDI in a North American setting and adapt for use as a self-report tool. Methods: Persons 18–65 years old from the population-based University of Manitoba IBD Research Registry were mailed a self-administered survey. This survey included the IBDDI and several scales that should correlate with a disability measure— the World Health Organization (WHO) Disability Assessment Scale (WHODAS) 2.0, Work and Social Adjustment Scale (WSAS), the Inflammatory Bowel Disease Questionnaire (IBDQ), and the K6—Kessler Emotional Distress Scale. We used Pearson correlation coefficients to assess construct validity, Cronbach's alpha to assess internal consistency, and Factor analysis to assess which of the IBDDI items likely belonged to a single IBD-related disability factor. Results: In response to the survey request, 1143 (46% of those contacted) participated (61% female, mean age 51, 52% with Crohn's disease). On an index scale from 0–100, 14% had a score ≥50 (extreme disability, 18% of those with Crohn's disease; 10% of those with ulcerative colitis). There were strong correlations between IBDDI and WSAS (0.76), WHODAS (0.76), K6 (0.73), and an inverse correlation with IBDQ (-0.86). The Cronbach's alpha was high (0.88). All but 2 items (number of liquid stools in the past week and arthritis/arthralgia) of the 14 identified for IBDDI loaded highly onto a single factor (factor loading > 0.40). Conclusions: The findings support the validity of this new self-report version of the IBDDI as a sound measure of disability in IBD.